What do medical students post online? Perception on medical professionalism in social media among medical students in Universiti Putra Malaysia - Faridah Idris,; Puteri Shanaz Jahn Kassim,; Sayyidah Aqilah Ridzuan,; Muhammad Afwan Shamsulbaharin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The fast development and accessibility of social media has created an important potential for improvements in the medical field. However, it may also increase the risk of unprofessional conduct among its users including medical students. This study aimed to determine the pattern of social media usage and the self-perceived online professionalism among medical students in one public university in Malaysia. A cross sectional study using a questionnaire was conducted. The questionnaire consisted of participant's demographic details and perception of professionalism on social media usage, using a 5-point Likert scale. The descriptive data analysis was done using SPSS V21.0. Results showed majority (80-93%) denied making postings related to defamation, racism, gender discrimination, potential breach of confidentiality and bad behaviour. 30% shared their social media accounts and postings to public audience and 22% will accept their patients as friends or followers. Most students denied any improper posting related to potential unprofessional statements and behaviour hence perceived as still guarding their online professional conduct. However, some are still not sure about issues related to privacy settings and doctor-patient boundaries on social media. Hence, it is important to educate medical students regarding online medical professionalism and the potential challenges associated with online interaction via social media.